HUBUNGAN AKTIVITAS FISIK DENGAN INTENSITAS NYERI SENDI LUTUT PADA LANSIA DI PUSKESMAS LUBUK BUAYA PADANG - Hanum Widya Arif; Birman, Yuliza; Rini Yulia (Nusantara Hasana Journal, 2025)
Elderly (≥60 years) are susceptible to decreased physical, mental, and social functions that increase the risk of disease. Physical activity is important to prevent decreased body function, but if excessive can cause injury and worsen joint pain. This study aims to analyze the relationship between physical activity and the intensity of knee joint pain in the elderly at the Lubuk Buaya Padang Health Center. This study is an analytical observational study with a cross-sectional approach. The study sample was taken using the Correlative Analytical formula with a sample size of 50 respondents who met the inclusion and exclusion criteria. In respondents with heavy physical activity (19 people) experienced mild joint pain 5.3%, moderate pain 42.1%, and severe pain 52.6%. Respondents with moderate physical activity (16 people), 62.5% experienced mild joint pain, 12.5% ​​moderate pain, and 25% mild pain. Respondents with light physical activity (15 people), 40% mild pain, 40% moderate pain, and 20% mild pain. There is a relationship between physical activity and the intensity of knee joint pain with a p value of 0.006. There is a significant relationship between physical activity and the intensity of knee joint pain in the elderly at the Lubuk Buaya Padang Health Center